2023
DOI: 10.3390/foods12122303
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Mechanism of StWRKY6 in Potato (Solanum tuberosum)’s Cadmium Tolerance for Ensuring Food Safety

Abstract: The WRKY transcription factor plays a crucial role in plant stress adaptation. Our research has found that WRKY6 in Solanum tuberosum (potatoes) is closely related to cadmium (Cd) tolerance. Therefore, investigating the mechanism of StWRKY6 in plant resistance to Cd toxicity is of great scientific importance for food safety. This research further analyzed the gene structure and functional regions of the nuclear transcription factor WRKY6 in potatoes, discovering that StWRKY6 contains W box, GB/box, ABRE, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The ability of cadmium to induce StWRKY6 transcription factors up-regulated the expression of a number of potential genes, including those involved in cadmium chelation APR2, DFRA, plant defences VSP2, PDF1.4, toxic substance efflux ABCG1, light morphology development BBX20 and auxin signal SAUR64/67. He et al demonstrated that these genes coordinate the regulation of cadmium tolerance in StWRKY6 overexpressing lines [89]. A new WRKY transcription factor GmWRKY142 positively regulating cadmium stress was identified by cai et al GmWRKY142 was highly expressed in roots and the expression of the gene was significantly up-regulated under cadmium stress, and overexpression of GmWRKY142 in Arabidopsis and soybean hairy roots significantly enhanced cadmium tolerance.…”
Section: Role Of Wrky Transcription Factors In Plant Response To Heav...mentioning
confidence: 99%
“…The ability of cadmium to induce StWRKY6 transcription factors up-regulated the expression of a number of potential genes, including those involved in cadmium chelation APR2, DFRA, plant defences VSP2, PDF1.4, toxic substance efflux ABCG1, light morphology development BBX20 and auxin signal SAUR64/67. He et al demonstrated that these genes coordinate the regulation of cadmium tolerance in StWRKY6 overexpressing lines [89]. A new WRKY transcription factor GmWRKY142 positively regulating cadmium stress was identified by cai et al GmWRKY142 was highly expressed in roots and the expression of the gene was significantly up-regulated under cadmium stress, and overexpression of GmWRKY142 in Arabidopsis and soybean hairy roots significantly enhanced cadmium tolerance.…”
Section: Role Of Wrky Transcription Factors In Plant Response To Heav...mentioning
confidence: 99%